Penciptaan Daya Tarik Visual dengan Menerapkan Komposisi Gambar dalam Produksi Program Musik Televisi â€œWeskaâ€ - Fadlilah, Mohammad Fikri; Oktora, Dina Dwika (Jurnal Ilmiah Multimedia dan Komunikasi, 2025)
The production of this television music program emphasizes the application of visual composition to create an optimal appeal. The process of creating works is carried out through three stages of production, namely pre-production, production, and post-production. In its application, the author uses various elements of image composition, such as headroom, look room, rule of thirds, and camera angle. The application of these elements aims to create visual balance and produce an attractive appearance for the audience. The application of composition principles in the Production of the Television Music Program "Weska" is able to create visual appeal and improve the quality of visuals and viewing experiences, both in the context of musical performances and direct interaction between musicians and audiences.